2018
DOI: 10.1093/ejcts/ezy128
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular outflow tract reconstruction using a polytetrafluoroethylene conduit in Ross patients†

Abstract: The PTFE conduit demonstrates acceptable haemodynamic results at the mid-term follow-up and could be considered as an alternative substitute for RVOT reconstruction during the Ross procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
7
0
2
Order By: Relevance
“…The clinical results from Japan were excellent. However, this artificial conduit was only used in a handful of heart centers outside of Japan ( 54 , 55 ). In the last decade, the application of 0.1 mm thick ePTFE for RVOT reconstruction has gradually increased in the form of bicuspid valves directly sutured into RVOT ( 56 , 57 ), or bicuspid/tricuspid valved conduits without bulging sinuses ( 32 , 58 ).…”
Section: Clinical Outcomes Of Available Conduitsmentioning
confidence: 99%
“…The clinical results from Japan were excellent. However, this artificial conduit was only used in a handful of heart centers outside of Japan ( 54 , 55 ). In the last decade, the application of 0.1 mm thick ePTFE for RVOT reconstruction has gradually increased in the form of bicuspid valves directly sutured into RVOT ( 56 , 57 ), or bicuspid/tricuspid valved conduits without bulging sinuses ( 32 , 58 ).…”
Section: Clinical Outcomes Of Available Conduitsmentioning
confidence: 99%
“…PTFE valved conduits show excellent hemodynamic performance in preclinical in vitro and in vivo experiments ( 95 97 ). The results of mid-term clinical trials showed less need for further intervention and severe valvular dysfunction ( 98 , 99 ), especially in valvular regurgitation ( 100 ). And the failure incidence of this conduit is lower than that of autologous pericardial valved conduit operation ( 101 ).…”
Section: Xenograft Valved Conduits and Other Possible Alternativesmentioning
confidence: 99%
“…Surgery for congenital heart disease often requires implantation of conduits for repair, conduits which do not have growth potential and will require multiple repeat interventions or operations [1][2][3][4]. There is an ongoing search for bioactive conduits that grow with a patient, potentially eliminating the need for repeated surgical procedures to replace faulty valves and outgrown conduits [5][6][7][8][9][10][11][12][13][14][15]. We have developed a unique cardiovascular conduit with an anisotropic capacity for stretching, by manipulating an expanded polytetrafluoroethylene (ePTFE) polymer sheet with directionally dependent expansion properties.…”
Section: Introductionmentioning
confidence: 99%